Respuesta :

( 1, 7 )

Explanation:
There are actually two ways to solve this; substitution and elimination ( I'm just going to use substitution though)

Since your equations are
y = 5x + 2
3x = -y + 10
You can just plug in the y into the second equation like so;
3x = - ( 5x + 2 ) + 10
Now you have to distribute the negative sign to 5x and 2
Your equation should now look like this;
3x = -5x - 2 + 10
Since you want to keep common numbers together, you need to add 5x to both sides (you can also move -2 and 10 to the left and 3x to the right, but it takes more steps)
3x + 5x = -2 + 10
3x + 5x = 8x and -2 + 10 = 8  (It's the same as 10 - 2 )
8x = 8, in order to get x you need to get x by itself- in order to do this you have to divide both sides by 8
8x / 8 = x
8 / 8 = 1
x = 1
In order to get y you can plug x in to either equation, but I'm going to use the first equation
y = 5(1) + 2
y = 5 + 2
y = 7
x = 1, y = 7
( 1, 7)





Answer:

1,7 on 2020

Step-by-step explanation:

ACCESS MORE